Managing product innovation - Woodside, Arch G. (Elsevier JAI, 2005)
Historical research on firm-level innovation behavior results in the following main insight: firm-level decisions focusing on innovations are critical, difficult, and often result in failure to act. While acceptance is widespread among executives that firms must innovate radically as well as incrementally, success by firms mostly nurtures inertia and eventual failure rather than search and adoption of new superior technologies. What does it take to craft and maintain successful radical NPD programs? "Managing Product Innovation (MPI)" explains why both manufacturing and customer firms usually reject superior new technologies and how competitors new to the industry become successful (by focusing on previously unnoticed customers and offering higher performance with lower costs via the radically new technologies). "MPI" provides worthwhile answers on what specific actions executives in established and new firms can adopt to achieve successful radical NPD programs. Related to managing new NPD processes successfully and additional strategic marketing issues, the following few thoughts summarize the wisdom that Volume 13 elaborates upon: leverage interfirm relationships; pay attention to products that can be co-created by interfirm networks; think and act globally via personal contacts; stay complex and be uncomfortable with success; evaluate NPD performance using a life cycle perspective; and, identify upstream as well as direct influences on NPD performance.
Keywords: New products -- Management.; Production & quality control management.; Business & Economics -- Marketing -- General.; elektronické knihy; electronic books